HUBUNGAN KETEPATAN TERMINOLOGI MEDIS DENGAN KEAKURATAN PENGODEAN BERDASARKAN ICD-10 DI RUMAH SAKIT SECARA STUDY LITERATURE REVIEW - Deni Maisa Putra; Yulfa Yulia; Rahmadhani Rahmadhani; Athiyah Holindra (Universitas Hang Tuah, 2022)
Background: Accurate coding using appropriate diagnosis writing with appropriate medical terminology. And help the coding officer to code the disease according to ICD-10. This study aims to determine the relationship between medical terminology and the accuracy of coding based on ICD-10 in hospitals. Methods: The method used is a literature study carried out by describing the facts that exist and then being analyzed. Searching for articles through Google Scholar, with inclusion and exclusion criteria, the final results obtained 5 analyzed journals. Furthermore, the analysis is carried out by looking at the compare, contrast, critize, synthesize, summarize. Result: The results of this literature review show that from the 5 journals that have been analyzed there are 3 journals that have medical terminology accuracy with a percentage of more than 50%, 4 journals that have coding accuracy with a percentage of more than 50%, and 4 journals that have a relationship between terminology accuracy. Medical with coding accuracy. Conclusion: Based on the results of the literature review, it can be concluded that there is a need for uniformity and consistency in the use of medical terminology according to ICD-10 to further improve the accuracy of the code. So there should be communication between the coder and the doctor so that the perception between the two is the same and produces an accurate code.